Training Venusians or Martians?: Earthly explanations for gender differences. Issue 1 (5th January 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Training courses for workers are a vital part of an organization's efforts to keep ahead of the game. Gone are the days when people trained for a job and then said "goodbye" to learning for ever. Now continuous training – providing educational opportunities for employees to better understand their role and meet new challenges, particularly those that occur in a dynamic marketplace and as a result of technological advances – ought never to be overlooked or avoided. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.